The generalized order-kNarayana's cows numbers - Bilgici, Göksal (Walter de Gruyter GmbH, 2016)
AbstractNarayana’s cows problem is a problem similar to the Fibonacci’s rabbit problem. We define the numbers which are the solutions of this problem as Narayana’s cows numbers. Narayana’s cows sequence satisfies the third order recurrence relationNr=Nr−1+Nr−3with initial conditionN0=N1=N2= 1. In this paper, we define a new recurrence which is called generalized order-kNarayana’s cows sequence and by using this generalization and some matrix properties, we give some identities related to the Narayana’s cows numbers.
Keywords: 16. Peace & justice